Recognizing the dimensions and components of school social responsibility in order to achieve the appropriate mode - mahmood noori; kolsum nami; mahdi bagheri (مدیریت و چشم انداز آموزش)
Abstract The aim of the present study is to identify the dimensions and components of school social accountability in order to achieve an appropriate model. The research method is applicable in terms of its purpose, and qualitative in terms of its implementation method, and of data-based theory. The statistical population of the study includes 15 experienced school principals and vice principals, and the samples were selected using the snowball sampling method, and sampling continued until the research reached theoretical saturation and adequacy. Semi-structured interviews were used to collect data. Using the results of the study of theoretical foundations and research background and the content analysis of the interviews, the dimensions of social accountability of schools were identified and, through 3 stages of open coding, axial coding and selective coding, the model of the components of school social accountability was presented in 6 main categories of causal conditions, axial phenomenon (exploration of the components and dimensions of school social accountability: including 3 main categories of goals, characteristics, implementation method and 6 subcategories), causal conditions, strategies, contexts, intervening conditions and consequences of social accountability for use in schools. The results of this study show that; school social accountability refers to its main and central beneficiary, namely the student. Organizations, including educational organizations such as schools, are in a network of relationships with stakeholders, and the recognition and method of interaction with stakeholder groups in the organization's activities are important. Introduction School is one of the most effective spaces for education, promoting a culture of participation, and crystallization of students' personality and accountability. Humans are social beings and from the moment of birth to the end of their lives, they live in society and constantly interact with other people. They must always learn how to live in society and satisfy their needs. For this, it is necessary to learn social skills. The individual learns these skills during the socialization process, and learning them correctly can lead to the formation of social accountability (Chorli et al., 2016). Today, developing societies need responsible and self-sufficient people, and today's people need to accept accountability for their lives and destiny more than ever. In fact, one of the important goals of education is to raise responsible people with a high sense of social participation. Therefore, teaching accountability and, subsequently, discipline of children and adolescents by parents and school officials leads to the upbringing of responsible and service-oriented youth (Movalat & Dehdari, 2018). Social accountability is the moral principle by which an organization or individual participates in social activities to improve the lives of others (Păceşilă, 2018). A school's social accountability is the voluntary responsibility that school members exercise towards society and the environment by accepting ethical principles, developing democratic and sustainable values, transparent and ethical behavior in active voluntary participation, self-learning socially responsible behavior, and a commitment to considering the needs of stakeholders within the framework of international laws and standards (Augustiniene et al, 2015). To this end, a school can, by utilizing specialized forces, allocating necessary facilities, and creating appropriate and diverse scientific, sports, cultural, etc. programs for all students, in addition to transferring knowledge and skills, have a significant impact on the behavior and socialization of individuals and their adaptation to social ethics through the transfer of desirable and appropriate social values, norms, and attitudes (Kouhi et al, 2015). Therefore, school social accountability can support a two-way communication and effective cooperation between students and the educational environment, which in turn increases student participation in school activities. Therefore, the purpose of the present study is to design a school social accountability model with the approach of increasing student participation in school activities. Therefore, in this research, we seek to answer the question: how to recognize the dimensions and components of school social accountability in order to achieve an appropriate model? Theoretical Framework School Social Accountability A school's social accountability is a voluntary responsibility that school members have towards society and the environment by accepting ethical principles, developing democratic and sustainable values, transparent and ethical behavior in active voluntary participation, self-education, socially responsible behavior, and a commitment to considering the needs of stakeholders within the framework of international laws and standards (Poodineh et al, 2019). Research Background Kazemi Mohammadi & Begum (2023) conducted a study titled "The Relationship Between Academic Negligence in Students and Teacher's Accountability". The results of the study showed that there is a significant relationship between teacher's accountability and students' academic negligence, and the greater the teacher's accountability, the less academic negligence in students will be, so by selecting responsible teachers, the level of academic negligence in students can be reduced. Razaghi et al, (2023) conducted a study titled "The Effectiveness of Social Accountability-Based Education on Students' Unproductive Academic Behaviors". The results showed that social accountability-based education reduced students' unproductive academic behaviors and all its components, including cheating and plagiarism, alcohol consumption, drug use, discriminatory behavior, absenteeism, procrastination, deviant behavior, and lethargy; and the results remained in the follow-up phase. Research Methodology The research method is applicable in terms of its purpose, and qualitative in terms of its implementation method, and of data-based theory. The statistical population of the study includes 15 experienced school principals and vice principals, and the samples were selected using the snowball sampling method, and sampling continued until the research reached theoretical saturation and adequacy. Semi-structured interviews were used to collect data. Research findings Using the results of the study of theoretical foundations and research background and the content analysis of the interviews, the dimensions of social accountability of schools were identified and, through 3 stages of open coding, axial coding and selective coding, the model of the components of school social accountability was presented in 6 main categories of causal conditions, axial phenomenon (exploration of the components and dimensions of school social accountability: including 3 main categories of goals, characteristics, implementation method and 6 subcategories), causal conditions, strategies, contexts, intervening conditions and consequences of social accountability for use in schools. The results of this study show that; school social accountability refers to its main and central beneficiary, namely the student. Organizations, including educational organizations such as schools, are in a network of relationships with stakeholders, and the recognition and method of interaction with stakeholder groups in the organization's activities are important. Conclusion The present study was conducted with the aim of identifying the dimensions and components of school social accountability in order to achieve an appropriate model. The results of this study are consistent with the results of Kazemi Mohammadi & Begum (2023), Razaghi et al, (2023), Hoshangi Shayan & Salarifar (2023), de Almeida et al, (2023), Alfirević et al, (2023), and Lee et al, (2023). Kazemi Mohammadi & Begum (2023) showed that there is a significant relationship between teachers' accountability and students' academic negligence, and the greater the teachers' accountability; the less academic negligence will be in students. Therefore, by selecting responsible teachers, the level of academic negligence in students can be reduced. According to the results of the study, the following suggestions were made: 1- The need to plan for active participation of student: The results show that in order to develop social accountability in students, programs should be developed that encourage them to actively participate in school activities. This participation can include group activities, leadership roles, and positive social interactions. 2- The impact of the educational environment: Emphasizing the importance of the educational environment and interactions within the school shows how this environment can affect the personal and social development of students. Creating a collaborative and supportive atmosphere in the school can help strengthen a sense of accountability and belonging to society.